Trans‐Platinum(II) Thionate Complexes: Synthesis, Structural Characterization, and in vitro Biological Assessment as Potent Anticancer Agents. Issue 10 (28th August 2019) - Sakamaki, Yoshie; Ahmadi Mirsadeghi, Hasti; Fereidoonnezhad, Masood; Mirzaei, Faezeh; Moghimi Dehkordi, Zahra; Chamyani, Samira; Alshami, Mia; Abedanzadeh, Sedigheh; Shahsavari, Hamid R.; Beyzavi, M. Hassan
Abstract: A series of Pt(II) complexes trans ‐[Pt(PPh2 allyl)2 ( κ 1 ‐S‐SR)2 ], 1, PPh2 allyl=allyldiphenylphosphine, SR=pyridine‐2‐thiol (Spy, 1 a ), 5‐(trifluoromethyl)‐pyridine‐2‐thiol (SpyCF3 ‐5, 1 b ), pyrimidine‐2‐thiol (SpyN, 1 c ), benzothiazole‐2‐thiol (Sbt, 1 d ), benzimidazole‐2‐thiol (Sbi, 1 e ), were synthesized. They were characterized by NMR, HR ESI‐MS, and X‐ray crystallography. Treatment of human cancer cell lines (A549, SKOV3, MCF‐7) with these complexes resulted in promising antitumor effects in comparison with cisplatin. These compounds showed suitable selectivity between tumorigenic and non‐tumorigenic (MCF‐10 A) cell lines. Analyses of cell cycle progression and apoptosis were conducted for 1 a, the most cytotoxic compound, to screen dose/time response and to study the antiproliferative mechanism. An electrophoresis mobility shift assay was performed to assess the direct interaction of 1 a with DNA and the strong genotoxic ability was indicated through the comet assay method. Abstract : Promising metallodrugs : trans ‐configured Pt(II) complexes bearing phosphane and heterocyclic thiolates were designed in order to improve the therapeutic effect of platinum‐based prodrugs. The complexes were screened against three human cancer cells and for DNA interaction, and were found to have promising antitumor effects. Analyses of cell cycle progression and apoptosis were conducted to screen dose/time response and study the antiproliferative mechanism.